Noise and vibration analysis : signal analysis and experimental procedures - Brandt, Anders, ....- (Chichester : Wiley, 2011)
"Noise and Vibration Analysis adopts a practical learning approach, building upon two existing class-note type books that have been used by the author for 10 years of teaching two academic courses"--
Frequency Response -- 13.6 Coherent Output Power -- 13.7 The Coherence Function in Practice -- 13.8 Impact Excitation -- 13.9 Shaker Excitation -- 13.10Examples of FRF Estimation -- No Extraneous Noise -- 13.11Example of FRF Estimation -- With Output Noise -- 13.12Examples of FRF Estimation -- With Input and Output Noise -- 13.13Chapter Summary -- 13.14Problems -- References -- 14 Multiple-Input Frequency Response Measurement -- 14.1 Multiple-Input Systems -- 14.2 Conditioned Input Signals -- 14.3 Bias and Random Errors for Multiple-Input Systems -- 14.4 Excitation Signals for MIMO Analysis -- 14.5 Data Synthesis and Simulation Examples -- 14.6 Real MIMO Data Case -- 14.7 Chapter Summary -- 14.8 Problems -- References -- 15 Orthogonalization of Signals -- 15.1 Principal Components -- 15.2 Virtual Signals -- 15.3 Noise Source Identification (NSI) -- 15.4 Chapter Summary -- 15.5 Problems -- References -- 16 Advanced Analysis Methods -- 16.1 Shock Response Spectrum -- 16.2 The Hilbert Transform -- 16.3 Cepstrum Analysis -- 16.4 The Envelope Spectrum -- 16.5 Creating Random Signals With Known Spectral Density -- 16.6 Operational Deflection Shapes -- ODS -- 16.7 Introduction to Experimental Modal Analysis -- 16.8 Chapter Summary -- 16.9 Problems -- References -- References -- A Complex Numbers -- B Logarithmic Diagrams -- C Decibel -- D Some Elementary Matrix Algebra -- References -- E Eigenvalues and the SVD -- E.1 Eigenvalues and Complex Matrices -- E.2 The Singular Value Decomposition (SVD) -- References -- F Organizations and Resources -- Index .
Includes bibliographical references and index.
Keywords: Vibration -- Mathematical models; Noise -- Mathematical models; Acoustical engineering; Stochastic analysis; Signal processing